Anti-Obesity Potential of Secamone afzelii K. Leaf and Vine Ethanol Extract: Insights into Lipase Inhibition and Secondary Metabolites - Franklyn Nonso Iheagwam; Gloria Aniedi Itina; Oyinkansola Ayobolanle Faluyi; Mercy Bella-Omunagbe; Samuel Akpoyowvare Ejoh (Sci)
Pancreatic lipase is an enzyme crucial for breaking down fats through hydrolysis, and inhibiting it is important for managing obesity. This study evaluated the lipase inhibitory profile of the leaf (SALE) and vine (SAVE) of Secamone afzelii, explored the modes of inhibition, identified the primary compounds responsible for this effect, and examined their molecular interactions with lipase using in vitro and in silico techniques. SALE (IC50: 0.41 ± 0.02 mg/mL) exhibited higher lipase inhibitory activity compared to SAVE (IC50: 0.95 ± 0.05 mg/mL), although it was significantly lower than orlistat (IC50: 0.07 ± 0.00 mg/mL) across all concentrations. S. afzelii extracts inhibited lipase activity through an uncompetitive mode of inhibition. Gas chromatography-mas spectroscopy identified 54 and 47 compounds in SALE and SAVE, respectively, with 9,12-octadecadienoic acid (Z, Z)-, n-hexadecanoic acid and 4S,6R-dimethyl-7R-hydroxynonan-3-one identified as the most abundant compounds in both extracts. The binding energy of the top five ligands from S. afzelii ranged from −7.7 to −6.6 kcal/mol, outperforming that of orlistat (−4.4 kcal/mol). The ligands and orlistat had similar binding poses stabilised by hydrogen and π interactions with CYS299, SER301, CYS304, ASN425 and VAL426. These compounds were predicted to possess promising pharmacokinetic, lipophilic and hydrophilic properties. These results offer insights into the traditional use of S. afzelii for treating obesity and valuable information on potential drug candidates that can be optimised for combating this disease.